Is skewed X inactivation responsible for symptoms in female carriers for adrenoleucodystrophy? - Watkiss, E (1993)
A study of X inactivation in 12 female carriers for adrenoleucodystrophy showed no evidence that skewed patterns are related to clinical manifestation. Other possible mechanisms to explain manifestation in females are considered.